Gen Z and Paylater: Analysis of Purchase Decisions on the E-Commerce Platform in Samarinda City (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
The rapid development of digital technology, especially after the COVID-19 pandemic, has brought changes to people's behavior and lifestyle with the trend of digital payments. One of the advances in digital financial services technology is PayLater, a Fintech innovation that offers easy transactions in the form of loans and installments without a credit card. This study aims to analyze the influence of transaction convenience and risk perception on purchasing decisions using the PayLater feature on e-commerce platforms among Generation Z in Samarinda City. This study uses a quantitative approach with associative methods and multiple linear regression analysis using SPSS 27. The method used is purposive sampling to obtain a sample of 100 respondents from Generation Z in Samarinda City, aged 18-28 years, who have used PayLater on e-commerce platforms. The findings show that transaction convenience (X1) has a positive and significant effect on purchasing decisions, but risk perception (X2) does not have a significant effect on purchasing decisions. At the same time, both variables have a significant effect on purchasing decisions. The findings of this study are expected to provide valuable insights for the PayLater feature to design more effective strategies to improve customer satisfaction and transaction experience.